Pengembangan Media Digital Game-Based Learning (DGBL) untuk Meningkatkan Kemampuan Berpikir Kronologis Siswa dalam Pembelajaran Sejarah di SMA - Dicky Irawan; Ofianto Ofianto; Aisiah Aisiah (RC-INSTITUT, 2019)
Background of the research is not yet providing the media emphasis on the aspect of learning to think chronologically. This research aims to: 1) Developing media DGBL viable and practical learning in history. 2) Reveal the effectiveness of media Digital Game-based Learning (DGBL) in improving the chronological thinking ability of students. This development research using model ADDIE (Analyze, Design, Development, Implementation, and Evaluation). The subject of the trial consists of 29 SMAN 1 Padang Panjang of Class XI of SCIENCES 6. The eligibility test is done through assessment of expert material and 2 media expert. In addition, the test is also done by two people the practicalities of history teachers and 29 students to see the practicality of DGBL media. The results indicate that the feasibility of the development of media based on expert assessment of materials, techniques and instruments of data collection, and data analysis to Digital Game-Based Learning (DGBL) is well worth the use (average score of 4.18 research), while According to a feasibility assessment of media experts that the media very worthy DGBL used (average score of 4.26). Research products are effective in improving students ability to think chronologically with n-gain 0.67 (categorize your medium). Product Media DGBL rated very practical by teachers and students (mean score 4.68 and 4.6).